High‐Performance, Long‐Life, Rechargeable Li–CO2 Batteries based on a 3D Holey Graphene Cathode Implanted with Single Iron Atoms. Issue 16 (28th February 2020) - Hu, Chuangang; Gong, Lele; Xiao, Ying; Yuan, Yifei; Bedford, Nicholas M.; Xia, Zhenhai; Ma, Lu; Wu, Tianpin; Lin, Yi; Connell, John W.; Shahbazian‐Yassar, Reza; Lu, Jun; et al.
Abstract: A highly efficient cathode catalyst for rechargeable Li–CO2 batteries is successfully synthesized by implanting single iron atoms into 3D porous carbon architectures, consisting of interconnected N, S‐codoped holey graphene (HG) sheets. The unique porous 3D hierarchical architecture of the catalyst with a large surface area and sufficient space within the interconnected HG framework can not only facilitate electron transport and CO2 /Li + diffusion, but also allow for a high uptake of Li2 CO3 to ensure a high capacity. Consequently, the resultant rechargeable Li–CO2 batteries exhibit a low potential gap of ≈1.17 V at 100 mA g −1 and can be repeatedly charged and discharged for over 200 cycles with a cut‐off capacity of 1000 mAh g −1 at a high current density of 1 A g −1 . Density functional theory calculations are performed and the observed appealing catalytic performance is correlated with the hierarchical structure of the carbon catalyst. This work provides an effective approach to the development of highly efficient cathode catalysts for metal–CO2 batteries and beyond. Abstract : A highly efficient cathode catalyst for rechargeable Li–CO2 batteries is successfully synthesized by implanting single iron atoms into 3D porous carbon architectures, consisting of interconnected N, S‐codoped holey graphene sheets. The unique 3D hierarchical architecture can not only facilitate electron transport and CO2 /Li‐ion diffusion, but also enables a high uptake of Li2 CO3 to ensure a high capacity.